Coalition and connection in games : problems of modern game theory using methods belonging to systems theory and information theory - Guiasu, Silviu; Malita, Mircea (Pergamon Press, 1980)
Coalition and Connection in Games: Problems of Modern Game Theory using Methods Belonging to Systems Theory and Information Theory focuses on coalition formation and on connections occurring in games, noting the use of mathematical models in the evaluation of processes involved in games.